Dynamical and structural modifications of staphylococcal nuclease on C-terminal truncation - Kataoka, Mikio; Smith, Jeremy C. (Physica. B, Condensed matter, 1999)
Truncation of the 13 C-terminal residues of Staphylococcal nuclease leads to the disordering of the protein which nevertheless retains its capacity to function and recovers its native structure on inhibitor binding. To probe structural and dynamical changes on truncation, we combined neutron scattering techniques and molecular dynamics simulations. Both the experiments and simulations indicate that truncation leads to an increase in the amplitude of the local internal motions. The simulations also provide evidence for rapid denaturation of the protein on truncation and transmission of the perturbation to the active site, suggesting that the structures of the C-terminal residues and the active site are interdependent. The implications of the results for the relationship between flexibility and folding of the native protein are hereafter discussed.